Epistemic Goals of Scientific Inquiry: An Explanation Through Virtue Epistemology - Mikhail Khort (Philosophies)
The paper examines the integration of virtue epistemology into the philosophy of science, emphasizing its potential to deepen our understanding of scientific inquiry. The article begins by considering the limitations of traditional epistemological frameworks that focus on beliefs. The discussion is set in the context of the “value turn” in contemporary epistemology. Arguments are made to move towards recognizing the significance of intellectual virtues and the nature of epistemic agents. The current gaps in definitions of intellectual virtues about reliabilist and responsibilist approaches are examined and conceptual steps are proposed to bridge these gaps. It is suggested that the local and general epistemic goals of science should be clearly distinguished and then different ways of knowing should be attributed to these goals. These ways of knowing are proposed to be seen as exemplifying the realization of reliable skills and intellectual character traits. In sum, the article argues that adopting a virtue epistemology not only enriches the discourse on scientific knowledge but also promotes a culture of responsibility and integrity in the scientific community.